Efficient Turbo Inter Leaver Based MIMO OFDM System For Low Complexity Outdoor Communication - Kumari, D. Lalitha; Prasad, M.N. Giri (International journal of engineering and advanced technology, 2019)
An arrangement of multiple antennas in both the receiver and transmitter called Multiple Input and Multiple Output (MIMO). The Orthogonal Frequency Division Multiplexing (OFDM) is enabled in MIMO system for high data wireless communications. Combination of both MIMO and OFDM Access (OFDMA) is a growing technology in next generation communication systems. In this work, the Bit Error Rate (BER) performance of MIMO-OFDMA is analyzed with Orthogonal Space Time Block Code (OSTBC), Maximum Ratio Combining (MRC) and Turbo coding scheme over flat fading channel are named as MIMO-MRC-OFDMA. OSTBC is a transmit diversity scheme, which is utilized for delivering an efficient transmission with high peak data rates that significantly improves the capacity of communication systems. Successively, the MRC diversity solves transmit and receive diversity from an OSTBC. MRC approach is applied in the receiving end for summing and weighing the received signals from the multiple paths. Besides, turbo coding scheme is utilized for error correction in a given code rate. The proposed system performance is evaluated in light of BER by varying the number of receive and transmit antennas such as 2×2, 2×4, 4×2 and 4×4.